GE_GERICHTE P/13853/2014 vom 11. Januar 2016 - GE Cour de justice (2016)
PRÉSOMPTION D'INNOCENCE; SÉJOUR ILLÉGAL; CONFISCATION(DROIT PÉNAL); FIXATION DE LA PEINE; CONCOURS D'INFRACTIONS | Cst.32.1; LEtr.115.1.b; CPP.268; CPP.10; CPP.135; CP.286; CP.47.1; CP.49.1